METRONIDAZOLE GEL EFFECT ON RATS WITH BACTERIA-INDUCED PERIODONTITIS - Muhamat Muhtar S. Abdurrohman; R. Rama Putranto (ODONTO : Dental Journal, 2020)
Background: Periodontitis is an inflammatory disease in the periodontal tissue and causes progressive tissue damage. Tissue Inhibitor of Matrix Metalloproteinases-1 (TIMP-1) is directly responsible for the pathogenesis of periodontal diseases. Topical application of the metronidazole gel as a therapy for periodontal diseases can be used for additional therapy. This study aimed to analyze the effect of Metronidazole gel on periodontitis based on TIMP-1 levels in bacteria-induced periodontitis in rats. Methods: Twenty Sprague Dawley rats weighing 170-200 gram aged two months. Rats were divided into two groups: the control group and Metronidazole gel (Ti-es Metronidazole gel, 0.45 mg). Metronidazole gel was topically applied to the gingival sulcus. The gingival crevicular fluid sample was taken on day 3 with periopaper subjected to the Tissue Inhibitor of Matrix Metalloproteinase-1 level evaluation using the ELISA Method. Results: Normal reference Tissue Inhibitor of Matrix Metalloproteinase 1 levels gingival crevicular fluid 0.156-10 ng/ml. Tissue Inhibitor of Matrix Metalloproteinase 1 gingiva crevicular fluid in control and metronidazole gel was 1.34 ng/ ml and 3.57 ng /ml. There was a significant difference between control and metronidazole gel group (p<0.005)Conclusion: The Application of Metronidazole gel affects TIMP-1 levels in periodontitis.